2016
DOI: 10.1103/physreva.93.022303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noise correlations on randomized benchmarking

Abstract: Among the most popular and well studied quantum characterization, verification and validation techniques is randomized benchmarking (RB), an important statistical tool used to characterize the performance of physical logic operations useful in quantum information processing. In this work we provide a detailed mathematical treatment of the effect of temporal noise correlations on the outcomes of RB protocols. We provide a fully analytic framework capturing the accumulation of error in RB expressed in terms of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
129
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 39 publications
(52 reference statements)
3
129
0
Order By: Relevance
“…The differences in the distribution of measured survival probabilities over sequences under these two noise models reproduces the central predictions of ref. 17 We compare the characteristics of the distributions themselves against analytic predictions for both slowly and rapidly varying noise, beginning with the measured expectation, E I ð Þ, and variance, V I ð Þ (Fig. 2b, c), finding good agreement by taking only the applied noise strength as an input into a theoretical model (see Supplementary Materials).…”
Section: Mapping Noise To Measured Error In Rbmentioning
confidence: 99%
See 4 more Smart Citations
“…The differences in the distribution of measured survival probabilities over sequences under these two noise models reproduces the central predictions of ref. 17 We compare the characteristics of the distributions themselves against analytic predictions for both slowly and rapidly varying noise, beginning with the measured expectation, E I ð Þ, and variance, V I ð Þ (Fig. 2b, c), finding good agreement by taking only the applied noise strength as an input into a theoretical model (see Supplementary Materials).…”
Section: Mapping Noise To Measured Error In Rbmentioning
confidence: 99%
“…Recent theoretical studies have demonstrated that measurements on RB sequences in the presence of temporal noise correlations, can produce a divergence between average and worst-case reported trace fidelities. 17,20 Thus we find that measurement outcomes for different RB sequences are characterised by distributions with distinctly different shapes depending on the temporal correlations in the noise. The standard practice of combining all measurements to extract an RB error rate, p RB , from the decay of the mean over all J-gate sequences as a function of J, results in a global ensemble average and does not take advantage of this information (formally, as the noise we implement exhibits temporal correlations, the value of p RB one extracts may not be meaningful as a measure of average Clifford gate error).…”
Section: Mapping Noise To Measured Error In Rbmentioning
confidence: 99%
See 3 more Smart Citations